Nitrogen fixation and foliar nitrogen do not predict phosphorus acquisition strategies in tropical trees. (10th August 2018) - Soper, Fiona M.; Nasto, Megan K.; Osborne, Brooke B.; Cleveland, Cory C.
Abstract: The mechanistic links between nitrogen (N) availability and investment in plant phosphorus (P) acquisition have important implications for plant growth, species distributions, and responses to CO2 fertilization under global change, especially in P‐poor tropical ecosystems. Currently, it is unclear whether investment in strategies that enhance plant P acquisition (arbuscular mycorrhizal, AM; colonization or root phosphatase activity, RPA) are determined primarily by phylogeny, or whether these strategies differ among N2 ‐fixing legumes and nonfixing plants as a result of differing N availability. We hypothesized that plant N status, which can vary widely independent of N fixation, correlates with investment in P acquisition, because: (a) N and P concentrations scale in plant tissue indicative of coupled demand and (b) plants with more N may have more resources available to allocate to acquisition strategies. We grew seedlings of eight tropical tree species from three families (including three N2 ‐fixing and one nonfixing legume) under greenhouse conditions in native forest soil for four months. Species represented almost the full range of foliar N observed in tropical trees. Neither foliar N nor P concentrations correlated with investment in P acquisition. Across all species, we found an inverse relationship between investment in AM colonization and RPA, but this trade‐off was unrelated to foliar N or P and did not differ between functional types (i.e., N2 fixers vs. nonfixers). Within legumes (family Fabaceae), two strategies were evident that were unrelated to fixation status. High‐fixing Inga and nonfixing Dialium displayed high foliar N and P concentrations and greater proportional investment in RPA versus AM, while lower fixing Ormosia species were characterized by lower foliar nutrient concentrations and proportionally more investment in AM. Synthesis. Investment in P acquisition strategies in tropical trees is not dependent on foliar N or functional group, but instead may be controlled in part by resource trade‐offs. High diversity in nutrient strategies between related species cautions again the use of simple functional groupings to draw conclusions about nutrient acquisition in tropical trees. Abstract : Although nitrogen and phosphorus are stoichiometrically coupled in foliage, we found no evidence that investment in phosphorus‐acquisition mechanisms is related to either foliar nitrogen or to the presence of nitrogen fixation in tropical tree seedlings. Instead, species show trade‐offs between P acquisition mechanisms (arbuscular mycorrhizal colonization and root phosphatase enzymes), and display diverse nutrient strategies, even within plant families.